2021
DOI: 10.1002/cnr2.1557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub genes in bladder cancer based on weighted gene co‐expression network analysis from TCGA database

Abstract: Background Muscular invasive bladder cancer (MIBC) is a common malignant tumor in the world. Because of their heterogeneity in prognosis and response to treatment, biomarkers that can predict survival or help make treatment decisions in patients with MIBC are essential for individualized treatment. Aim We aimed to integrate bioinformatics research methods to identify a set of effective biomarkers capable of predicting, diagnosing, and treating MIBC. To provide a new the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recently, CSRP1 has been proven as a prognostic gene in many cancers including cholangiocarcinoma [ 10 ], prostate cancer [ 11 , 24 ] and bladder cancer [ 25 ]. In addition, celecoxib present anti-cancer effect might contribute to inhibit CSRP1 gene expression in gastric cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CSRP1 has been proven as a prognostic gene in many cancers including cholangiocarcinoma [ 10 ], prostate cancer [ 11 , 24 ] and bladder cancer [ 25 ]. In addition, celecoxib present anti-cancer effect might contribute to inhibit CSRP1 gene expression in gastric cancer [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that PTPRN2 is frequently expressed in temozolomide-resistant glioblastoma [31] , and castration-resistant prostate tumors [32] , suggesting that PTPRN2 is a promising therapeutic target of cancer. Bioinformatics research has found that PTPRN2 differs between the lower (II and III) and high (IV) grade gliomas, with its expression being higher in grade IV glioblastomas [33] , and are linked to bladder cancer [34] , and leiomyosarcoma sarcomagenesis [35] , but detailed research is lacking. In-depth studies, it has been demonstrated that PTPRN2 is strongly related to poor OS in breast cancer patients, through resistance to apoptosis [17] , and promotes the metastatic ability of breast cancer cells [16] .…”
Section: Discussionmentioning
confidence: 99%
“…We utilized the WGCNA package in R to establish co-expressed gene modules and, notably, identified a significant gene module with the most robust correlation to lung cancer, as documented in Refs. 35 , 53 , 54 . Furthermore, we applied WGCNA to the selected genes to explore the intricate expression patterns that existed among them.…”
Section: Methodsmentioning
confidence: 99%